Costumer Value Creation Strategy Based On Company Internal Data - Sukwadi, Ronald; Suef, Mokh; Widawati, Enny; Lucky, Novryan (Teknik dan Ilmu Komputer, 2015)
AbstrakÃÂ Globalisasi ekonomi dan ketatnya persaingan merupakan tantangan baru bagi setiap perusahaan, terutama untuk usaha kecil menengah (UKM). UKM seharusnya dapat memuaskan pelanggan dengan meningkatkan kualitas produk. Dalam memperbaiki kualitas produk, metode survei sering dilakukan untuk memeroleh pendapat dan kebutuhan pelanggan. Namun, UKM di Indonesia dan negara-negara berkembang lainnya menghadapi masalah terkait dengan sumber daya dan pengarahan. Studi ini meneliti penggunaan data internal perusahaan sebagai input alternatif suara pelanggan menggantikan survei pelanggan. Hasil studi kasus pada industri makanan dan minuman menunjukkan bahwa suara konsumen yang didapat dari data internal lebih mudah bagi UKM dibandingkan dari survei pelanggan. Selanjutnya, Blue Ocean Strategy (BOS) and refined Kano model digunakan untuk menciptakan nilai pelanggan dan juga untuk memperoleh nilai dari pelanggan.ÃÂ Kata kunci:ÃÂ nilai pelanggan, data internal, model refined Kano,ÃÂ Blue Ocean Strategy, UKMÃÂ ÃÂ AbstractÃÂ Economic globalization and intense competition pose new challenges to all companies especially for small and medium enterprises (SMEs). SMEs should be able to satisfy their customers by improving the quality of their products. In improving the quality of products, survey methods are often conducted to obtain customer opinions and needs. However, SMEs in Indonesia and other developing countries often face problems implementing those survey methods due to lack of resources and direction. This study examines the use of companyÃ¢â¬â¢s internal data as an alternative input for the voice of customer (VOC) replacing a customer survey. The results of this case study in food and beverage industries show that the VOC from the companyÃ¢â¬â¢s internal data are much simpler than that of the customer need survey. Moreover, Blue Ocean Strategy (BOS) and refined Kano model are applied to create Customs value and to obtain value from the customers.ÃÂ Keywords: customer value, internal data, refined Kano model, Blue Ocean Strategy, SMEs